Resource Use After Unwanted Sexual Experiences in Undergraduates: A Comprehensive Evaluation of Factors Related to the Decision to Seek Help. Issue 7 (April 2021) - Fleming, C. J. Eubanks; Lynch, Kyle A.; Hakas, Maggie B.; Belanger, Elizabeth
The risk for sexual victimization in college is high, and although there can be significant mental and physical consequences for the survivor, resource utilization for this issue is extremely low. The current study used the frameworks of both the ecological model and the theory of planned behavior to examine factors related to resource use in undergraduate survivors of unwanted sexual experiences. The sample consisted of 217 undergraduates who reported at least one unwanted sexual experience while in college (89% female, 76.5% Caucasian, M age 19.6). Data were collected in an online survey from a private liberal arts college, and were analyzed using decision tree modeling. Results suggested that resource use was less related to demographic or event characteristics, but rather related to victim response to the event as well as perceptions about control over potential resource use. In addition to key assault prevention efforts, it is thus important to also support survivor mental health and self-efficacy postassault.